A Direct Numerical Simulation (DNS) Study on the Effect of Particle Configuration on Drag (Communications in Computational Physics, 2021)
Drag correlations are very important in particle-laden two-phase flow simulations. Some statistical studies have investigated extracting particle configurationfactors from simulation data to improve drag correlations. However, little attentionhas been paid to studying particle configuration effects on drag from the perspectiveof the flow mechanism. In this paper, a direct numerical simulation (DNS) methodbased on the second-order accurate immersion interface method is developed to provide highly reliable data. Then, the 'shielding' effect of the two-particle configurationon drag is comprehensively analysed under different angles, distances, and Reynoldsnumber $(Re)$ values, revealing that the complex configuration dependence of the draginfluence is attributed to the dominant flow mechanism, such as the 'pressure regionunit', 'nozzle', and 'wake' effects. Moreover, we study the 'superposition' effect of thethree-particle configuration on drag in a finite $Re$ range. The results show that whenthe surrounding particles do not directly shield each other, the drag influence calculated by pairwise linear superposition is close to the drag influence revealed by DNS.Otherwise, when the shielding phenomenon of the surrounding particles is obviousand the $Re$ is high, the drag influence of the nearest particle can represent the DNSresult.
Keywords: Particle-laden two-phase flow; direct numerical simulation; particle configuration; drag; flow mechanism.